The know-how of public leaders in collective politics - Díaz, Lucas (Emerald Publishing Limited, 2024)
Whether pushing for change at the hyper local level or at the international level, public leaders deploy a type of practice-based knowing that helps them advance their cause. Developing the concept of know-how as a more robust analyzable concept than has been offered in the contentious collective politics literature to date, Díaz explores how public leaders deploy this in collective contention in pursuit of desired social justice outcomes. Addressing a glaring omission that has left researchers unable to fully account for the ways in which public leaders can affect a group's ability to succeed in securing change, Díaz starts by defining what know-how is, and what it is not. Presenting real-life lessons through a practical analytical framework, the author uses data from interviews, participant observation and member ethnography of public leaders engaged in contentious collective politics in post-Hurricane Katrina New Orleans to explore the informal, social, strategic and operational dimensions of know-how. These cases offer lessons that can be learned by anyone pushing for systemic changes to social inequalities in their communities anywhere in the world. From small, local associations to national social movements, The Know-How of Public Leaders in Collective Politics demonstrates how we can make more meaningful assertions about what leaders do and how they do it to better push for systemic social change.
Keywords: Political leadership -- Research.; Equality -- Research.; Political Science -- Civil Rights.; Political leaders and leadership.; Human rights, civil rights.; elektronické knihy; electronic books